Meningitis as an Initial Presentation of COVID-19: A Case Report - Naz, Sidra; Hanif, Muhammad; Haider, Muhammad Adnan; Ali, Mukarram Jamat; Ahmed, Muhammad Umer; Saleem, Sana (Frontiers in Public Health, 2020)
In addition to common presenting symptoms of fever, fatigue, and mild respiratory symptoms like dry cough, patients with COVID-19 can also develop neurological manifestations like headache, anosmia, hyposmia, dysgeusia, meningitis, encephalitis and acute cerebrovascular accidents during the course of the disease. Although very rare, these neurological manifestations sometimes, are the sole initial presenting complaint of COVID-19. Likewise, in current case where the initial presenting symptoms were exclusive to meningitis and later on diagnosed with COVID-19, to make physicians and healthcare workers cognizant of such rare presentations in order to diagnose and manage these patients at the earliest to prevent the horizontal spread.